MATLAB-PROGRAM FOR LIGHT DISPERSION ON PRIZM AND "OWN DISCOVERIES" EDUCATIONAL METHOD - Gayev Y. (Kherson State University, 2018)
MATLAB-programming of physical problems is quite easy. It captures students, encourages them to overcome certain difficulties and obstructions on the way to a pleasant program with graphical interface. Students focus to physical problem formulation, choose mathematical tools required. This way they realize educational method «Path to own Discoveries» being propagated in last publication by the author. In this article, this is illustrated by creation of MATLAB-program that displays (imitates) white light dispersion to a «rainbow» when it passes through a glass prism. MATLAB provides capabilities of an «easy programming» that facilitates students to learn physics more effectively. Besides school laws of geometrical optics, they need to know only school geometry, trigonometry and basics of analytic geometry (namely, the topic «Line on a plane»). This article delivers a few exercises with algorithms and programming to the informatics lecturer. To the teacher of mathematics it provides convincing illustration for practical use of some its chapters (trigonometry, line equations etc.). Teacher of physics gets a model and the program for virtual computer experiments in optics. But the students, finally, get simple scientific and educational tools, term works etc. that display pleasure of sciences and their mutual intrinsic relationships.